Perencanaan Delicias Central Kitchen sebagai Mitra Mandiri Program Makan Bergizi Gratis di Kabupaten Sleman - Suparman Situmorang; Riani Prihatini Ishak (CV. Kalimasada Group, 2025)
This study analyzes the planning function of Delicias Central Kitchen (CK) as a prospective Independent Partner (Mitra Mandiri) in supporting the Free Nutritious Meal Program (MBG) in Sleman Regency, Indonesia. Using a descriptive qualitative case study, data were collected through in-depth interviews with three key informants (operations manager, head chef, and warehouse head), direct observation, and document analysis. Findings reveal that Delicias CK applies an integrated foodservice system based on the input–process–output–feedback model (Gregoire, 2017). Inventory management adopts FIFO and FEFO principles, while production follows a two-shift schedule with a one-way workflow, producing up to 3,500 portions per day. Although the standard operating procedures (SOPs) remain under finalization, quality assurance practices align with Hazard Analysis and Critical Control Points (HACCP). A SWOT analysis highlights strengths in infrastructure and community collaboration, weaknesses in digital reporting and menu rotation, opportunities for partnership with local SMEs, and threats related to supply fluctuations. Stakeholder mapping confirms active coordination among the kitchen, foundation, National Nutrition Agency, and beneficiary schools. In conclusion, Delicias CK demonstrates strong operational readiness as a public nutrition service partner, with recommendations to finalize SOPs, strengthen digital monitoring, and expand collaborative networks.